The impact additional of employee income and work discipline on employee performance: An empirical study at the Gorontalo Regency Social Service Agency - Sri Safrilla H Z Rivai; Heldy Vanni Alam; Melan Angriani Asnawi (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to analyze the effect of Additional Employee Income (TPP) and Work Discipline on Employee Performance at the Gorontalo Regency Social Service. The background of this study stems from the phenomenon of declining volume and quality of work output and low employee initiative over the past four years, indicating the need for an evaluation of factors influencing civil service performance. This study employs a quantitative method with an associative approach. The research population consisted of 30 employees, all of whom were sampled using a saturated sampling technique. Data were collected through questionnaires and documentation, then analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, partial t-tests, simultaneous F-tests, and the coefficient of determination (R²) with the assistance of SPSS version 20. The results reveal that Additional Employee Income has a positive and significant effect on Employee Performance. Similarly, Work Discipline also demonstrates a positive and significant effect on Employee Performance. Simultaneously, both variables significantly influence Employee Performance. The coefficient of determination indicates that 63.1% of the variation in Employee Performance can be explained by TPP and Work Discipline, while the remaining 36.9% is influenced by other factors outside the research model. These findings confirm that a balance between financial incentives and enforcement of work discipline is key to improving productivity, effectiveness, and the quality of public services at the Gorontalo District Social Service. Keywords: Work Discipline; Employee Performance; Additional Employee Income